2021
DOI: 10.3389/fevo.2021.739550
|View full text |Cite
|
Sign up to set email alerts
|

A Hollow Argument: Understory Vegetation and Disturbance Determine Abundance of Hollow-Dependent Mammals in an Australian Tropical Savanna

Abstract: Native mammals are suffering widespread and ongoing population declines across northern Australia. These declines are likely driven by multiple, interacting factors including altered fire regimes, predation by feral cats, and grazing by feral herbivores. In addition, the loss of tree hollows due to frequent, intense fires may also be contributing to the decline of hollow-dependent mammals. We currently have little understanding of how the availability of tree hollows influences populations of hollow-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
3
5
0
Order By: Relevance
“…Gray circles indicate observed data values and are darker when repeated observations occur at the same point. Davies et al, 2017;Penton et al, 2021), cat occupancy (Davies et al, 2017;Stobo-Wilson et al, 2020a), fire 'activity' or extent (Lawes et al, 2015;Stobo-Wilson et al, 2020a) and the presence of feral livestock (Legge et al, 2019). Our study also supported the hypothesis that site-scale disturbance and habitat features are more directly important to local mammal populations than broader landscapescale (see above) or regional-scale (as per Radford et al, 2020a;Stobo-Wilson et al, 2020a) fire mosaic attributes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Gray circles indicate observed data values and are darker when repeated observations occur at the same point. Davies et al, 2017;Penton et al, 2021), cat occupancy (Davies et al, 2017;Stobo-Wilson et al, 2020a), fire 'activity' or extent (Lawes et al, 2015;Stobo-Wilson et al, 2020a) and the presence of feral livestock (Legge et al, 2019). Our study also supported the hypothesis that site-scale disturbance and habitat features are more directly important to local mammal populations than broader landscapescale (see above) or regional-scale (as per Radford et al, 2020a;Stobo-Wilson et al, 2020a) fire mosaic attributes.…”
Section: Discussionsupporting
confidence: 85%
“…This corroborates Stobo-Wilson et al (2020a) in finding that vegetation productivity was positively associated with mammal richness at broad scales except for when fires removed the cover. The importance of shrub cover as a model attribute for volcanic habitats also support previous findings for the threatened mammal Conilurus penicillatus in Melville Island savannas (Davies et al, 2017;Penton et al, 2021). The dynamic nature of ground layer vegetation highlights a key implied threat to savanna mammals in these open habitats.…”
Section: The Positive Influence Of Site-scale Habitat Coversupporting
confidence: 82%
See 2 more Smart Citations
“…Of 17 studies of fire effects conducted in Northern Australia, 12 of which were experimental, six concluded that loss of cover explained significant small-mammal responses (Kutt and Woinarski, 2007;Legge et al, 2008;Kutt and Gordon, 2012;Leahy et al, 2015;Davies et al, 2017;Radford et al, 2021), five concluded that both cover and food resources were partly important as limiting factors (Lawes et al, 2015;McDonald et al, 2016;Ondei et al, 2020;Radford et al, 2020;Penton et al, 2021), and six studies were inconclusive (Pardon et al, 2003;Woinarski et al, 2004;Griffiths and Brook, 2014;Abom et al, 2016;Davies et al, 2018;Legge et al, 2019; Supplementary Table S1, Figure 2). One study found 90% direct mortality of small mammals from intense fires, with the individuals surviving being in unburned refuges (Legge et al, 2008).…”
Section: Northern Australiamentioning
confidence: 99%